2017
DOI: 10.1177/2151458517722104
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures in Centenarians: Has Care Improved in the National Hip Fracture Database Era?

Abstract: Introduction:The number of centenarians in the United Kingdom is increasing. An associated increase in the incidence of hip fractures in the extreme elderly population is expected. The National Hip Fracture Database (NHFD) initiative was introduced in 2007 aiming to improve hip fracture care. There is a paucity of literature on the outcomes of centenarians with hip fractures since its introduction. The aim of this study is to report our experience of hip fractures in centenarians in the era since the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…More and more researches have shown that elderly hip fracture induced systemic inflammatory response and ALI, which increased the incidence of pulmonary infection complications and mortality in the elderly patients [ 2 , 5 , 6 , 33 , 34 ]. Although many measures have been taken to deal with it, such as perioperative respiratory assessment and management, surgical technique amendment, and internal fixation instrument improvement, pulmonary infection rates still remain high in clinic; it is still the main cause of death in the elderly fracture patients [ 35 37 ]. As the important cause of lung infection complications, systemic inflammatory response and ALI induced by the elderly hip fracture have attracted more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…More and more researches have shown that elderly hip fracture induced systemic inflammatory response and ALI, which increased the incidence of pulmonary infection complications and mortality in the elderly patients [ 2 , 5 , 6 , 33 , 34 ]. Although many measures have been taken to deal with it, such as perioperative respiratory assessment and management, surgical technique amendment, and internal fixation instrument improvement, pulmonary infection rates still remain high in clinic; it is still the main cause of death in the elderly fracture patients [ 35 37 ]. As the important cause of lung infection complications, systemic inflammatory response and ALI induced by the elderly hip fracture have attracted more and more attention.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the higher baseline degree of cognitive impairment and dependency or the higher degree of in-hospital complications in this age group. 9 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Discrepancies have also been published regarding short and long-term outcomes. 6–8 , 11 , 12 A recent study including more than 4000 centenarians with hip fracture focused exclusively on complications during hospitalization, but did not include outcomes related to mortality or functional status in the first month after the fracture. 10 …”
Section: Introductionmentioning
confidence: 99%
“…This is at variance to a common notion that older individuals undergoing surgery for hip fractures are at increased risk of death. Previous studies did not include a comparator group (11)(12)(13), or used incompatible control groups, such as those comprising younger patients (9,10,14). Some studies also compared mortality with standardised mortality of the general population (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in the impact of hip fractures on an ageing population of patients, particularly those older than 90 years of age, and the implications for improving care with disability, survival and consequences for health economics (9)(10)(11)(12)(13). Hitherto, results from previous studies have been limited due to the smaller number of very old patients, so that these studies accumulated data from different centres where management procedures may differ (13).…”
mentioning
confidence: 99%